India's political economy responses to the global food price shock of 2007 - 08: Learning some lessons - Ashok Gulati; Shweta Saini (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
India's policy responses to the food price crisis were strong. Exports of basic staples were banned. Domestic support prices of wheat and rice were raised substantially. The urea price increases in global markets were absorbed through enhanced fertilizer subsidies. The government launched the National Food Security Mission in 2007-08 with an objective to raise grain production by 20 MMT over the subsequent five years. The results: India contained food inflation below 7 per cent in 2007-08; grain production increased by 42 MMT over five years leading to government's grain stocks touching 82 MMT in 2012. Backed by robust production and stock levels, rice exports surged when India freed up its exports in September 2011, making it a world leader in rice exports. However, policies followed during the crisis and eventually to combat it, resulted in a high fiscal deficit mainly because of the rising food and fertilizer subsidies, leading to double-digit food inflation after 2009-10. In retrospect, had India reviewed its export bans and opened up exports earlier, it could have avoided excessive grain stocks, reduced its fiscal deficit, and benefited global markets, leading to a win-win situation.
Keywords: Q17; Q18; F42; E60; 330; food security; trade; export bans; global food crisis; India; agriculture policy